2023
DOI: 10.1038/s41598-023-37781-y
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling geospatial distribution and genetic diversity of greenhouse whitefly, Trialeurodes vaporariorum (Westwood) from Himalayan Region

Abstract: The Greenhouse whitefly (GWF), Trialeurodes vaporariorum (Westwood) (Hemiptera: Aleyrodidae), is a destructive pest that affects protected cultivation worldwide. The Indian Himalayan region is particularly vulnerable to GWF introduction, invasion, and spread due to the expansion of protected cultivation and climate change. In this study, we collected 32 naturally occurring GWF populations, mainly from the Uttarakhand state in the Indian Himalayan region, to investigate the distribution pattern and genetic dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The species T. vaporariorum, known to inhabit greenhouses (Moraes et al, 2018;Perring et al, 2018), has now been discovered in open field conditions within cabbage, common bean, and passion fruit crops. This finding corroborates observations made by Lourenção et al (2008), who reported the presence of T. vaporariorum in vegetables in the state of São Paulo, and Paschapur et al (2023), who noted its natural occurrence in India. There have been reports of NW in Argentina, the United States, Martinique, Mexico, and Venezuela (Barbosa et al, 2014b).…”
Section: Resultssupporting
confidence: 92%
“…The species T. vaporariorum, known to inhabit greenhouses (Moraes et al, 2018;Perring et al, 2018), has now been discovered in open field conditions within cabbage, common bean, and passion fruit crops. This finding corroborates observations made by Lourenção et al (2008), who reported the presence of T. vaporariorum in vegetables in the state of São Paulo, and Paschapur et al (2023), who noted its natural occurrence in India. There have been reports of NW in Argentina, the United States, Martinique, Mexico, and Venezuela (Barbosa et al, 2014b).…”
Section: Resultssupporting
confidence: 92%
“…T. acaciae was recorded in India on subabul, with subsequent infestations observed on orchid trees, tamarind, rain trees and an unidentified pulse crop (Sundararaj and Vimala, 2018). The impact of T. vaporariorum extends to vegetables and ornamental species, requiring comprehensive management strategies, as outlined by Paschapur et al (2023).…”
Section: O N L I N Ementioning
confidence: 99%
“…The shift in damaging patterns, transitioning from greenhouses to open fields, raises significant concerns (Paschapur et al, 2023). A. floccissimus primarily infests citrus trees and may also feed on guava, mango, litchi and ornamental plants (Sundararaj et al, 2020).…”
Section: O N L I N Ementioning
confidence: 99%